Career Profiles of Generation Y and Their Potential Influencers - Cordeiro,Helena Talita Dante (2017)
Abstract This study aims to identify the predominant career profiles among Generation Y in Brazil and investigate the influence of demographic and professional characteristics in these profiles. Career profiles are defined as combinations of the presence of Boundaryless and Protean career attitudes. This study is descriptive, the sample is non-probabilistic and intentional and consists of 2,376 people. Cluster Analysis and Chi-square tests were used. The results show that people from Generation Y have a high presence of attitudes related to new careers and that these new careers are associated with high education and high income, mainly the Boundaryless career. However, there is a small portion of the sample that doesn’t present new career attitudes, indicating that this is just a movement and cannot be considered a reality for all studied subjects.